Telerehabilitation and telemonitoring interventions programs used to improving quality of life in people with cystic fibrosis: A systematic review - Ortiz Ortigosa, Lucía; Vinolo-Gil, Maria Jesus; Pastora-Bernal, José Manuel; Casuso Holgado, María Jesús; Rodríguez-Huguet, Manuel; Martín-Valero, Rocío (SAGE Journals, 2023)
Background: Cystic fibrosis causes mucus to build up in the lungs, digestive tract, and other areas. It is the most common chronic lung disease in children and young adults. It requires daily medical care. Before the COVID-19 pandemic, telerehabilitation and telehealth were used, but it was after this that there was a boom in these types of assistance in order to continue caring for cystic fibrosis patients. Objective: The objective is to evaluate the effect of telemedicine programs in people with cystic fibrosis. Methods: For the search, the PubMed, Scopus, Web of Science, PEDro, Cochrane, and CINAHL databases were used. Randomized controlled trials, pilot studies, and clinical trials have been included. The exclusion criteria have considered that the population did not have another active disease or that telemedicine was not used as the main intervention. This study follows the PRISMA statement and has been registered in the PROSPERO database (CRD42021257647). Results: A total of 11 articles have been included in the systematic review. No improvements have been found in quality of life, forced expiratory volume, and forced vital capacity. Good results have been found in increasing physical activity and early detection of exacerbations. Adherence and satisfaction are very positive and promising. Conclusions: Despite not obtaining significant improvements in some of the variables, it should be noted that the adherence and satisfaction of both patients and workers reinforce the use of this type of care. Future studies are recommended in which to continue investigating this topic.
Keywords: Fibrosis quística; Telemedicine; cystic fibrosis; exercise; telemonitoring; telerehabilitation